Geographic Disparities in Well-Being and Fiscal Expenditures in Thailand : 2000 vs. 2009 - Skoufias, Emmanuel (Taylor and Francis, 2013)
This article investigates (1) the extent to which the differences in the standard of living between regions in Thailand are due to differences in the returns to characteristics or differences in the characteristics themselves; and (2) whether the current allocation of fiscal expenditures by the central authorities is related to the main determinants of spatial disparities in welfare among the provinces. The analysis reveals that the lower level of welfare in the rural areas within any given region is primarily because of differences in characteristics of the population in rural vs. urban areas. Differences in returns generally account for the most part of the welfare differences between urban areas of different regions and Bangkok or rural areas of other regions compared with the rural northeast. The analysis of fiscal expenditures and their relation to welfare disparities suggests that there are many opportunities to improve the role of fiscal expenditure allocation by the central government as an instrument of addressing the needs of the provinces in terms of low returns.